DAMPAK KUALITAS LAYANAN ARTIFICIAL INTELLIGENCE TERHADAP LOYALITAS PELANGGAN PADA E-COMMERCE DI INDONESIA - Khairyanti, Rashinta Adelia; Syaharani, Puteri; Arafah, Willy (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2024)
The results of this research discuss the aim of investigating the influence of artificial intelligence (AI) chatbot service quality on customer loyalty in an organization. Through a sequential chain model of service quality loyalty, this research classifies AI chatbot service quality into nine attributes and develops a research model to explore the internal mechanisms of the influence of AI chatbot service quality on customer loyalty. These findings can assist organizations in increasing customer value perceptions, trust, satisfaction, and loyalty, as well as provide guidance in the development, adoption, and post-adoption of affective trust, and satisfaction. This research contributes to the understanding of service quality in the context of information systems (IS) and extends the sequential chain model of quality loyalty to the context of AI services. These findings can help organizations improve customer value perception, trust, satisfaction, and loyalty, as well as provide guidance in the development, adoption, and post-adoption of AI chatbots